2022
DOI: 10.1002/cam4.5141
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in Black‐White disparities in cancer surgery and cancer‐specific survival in the United States between 2007 and 2015

Abstract: Background The American Society of Clinical Oncology (ASCO) has strived to address racial/ethnic disparities in cancer care since 2009. Surgery plays a pivotal role in cancer care; however, it is unclear whether and how racial/ethnic disparities in cancer surgery have changed over time. Methods This cohort study included 1,113,256 White and Black cancer patients across 9 years (2007–2015) using patient data extracted from the Surveillance, Epidemiology, and End Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Our result concerning the increased likelihood of Black women with breast cancer to not receive surgery as treatment was also found in prior studies. 7,32,35,36 To our knowledge, no other studies have investigated potential mediators of the race effect on disparities in nonreceipt of surgery. In this study, the mediating impact of insurance status and neighborhood poverty were even less impactful for nonreceipt of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our result concerning the increased likelihood of Black women with breast cancer to not receive surgery as treatment was also found in prior studies. 7,32,35,36 To our knowledge, no other studies have investigated potential mediators of the race effect on disparities in nonreceipt of surgery. In this study, the mediating impact of insurance status and neighborhood poverty were even less impactful for nonreceipt of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies and statistical reports have documented racial (Black/White) disparities in breast cancer mortality/survival over several decades 2–5 . Despite knowledge of racial disparities in many cancer outcomes and corresponding efforts to redress these inequities, Black women still bear a significantly higher burden of breast cancer than White women 6,7 . We recently reported that although breast cancer survival had improved for all women in Florida and Black/White disparities had decreased, Black women still experienced over twice the rate of breast cancer death compared to their White counterparts in the most recent time period 8 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current therapeutic approaches for BC mainly consist of chemotherapy, hormone therapy, and surgery ( Aghanejad et al, 2013 ; Kadkhoda et al, 2022 ; Zhong et al, 2022 ). However, disadvantages such as adverse side effects for patients, drug resistance, and residual tumor cells greatly limit their therapeutic effect and may lead to cancer recurrence ( Waks and Winer, 2019 ; Kadkhoda et al, 2021 ).…”
Section: Photothermal Therapymentioning
confidence: 99%
“…Cancer is a leading cause of death worldwide, accounting for approximately 10 million deaths in 2020 [1,2]. Cancer treatments include chemotherapy, phototherapy, radiation therapy, and surgery [3][4][5][6][7][8][9][10][11][12]. Chemotherapy is a traditional treatment for cancer and can effectively treat cancer, even at low doses [13][14][15].…”
Section: Introductionmentioning
confidence: 99%